2014
DOI: 10.5812/aapm.17560
|View full text |Cite
|
Sign up to set email alerts
|

Propofol and Alfentanil in Treatment of a Patient With Episodic Cluster Headache

Abstract: Introduction:Cluster headache is a severe hemifacial pain with concomitant symptoms such as lacrimation, conjunctival congestion, and nasal discharge. Peripheral (to be a spectrum of trigeminal autonomic cephalgia) and central (hypothalamus) disorders have been suggested to be involved. Several modalities have been recommended to prevent or alleviate this devastating headache.Case Presentation:In this case report, we presented a young man with an acute cluster headache who responded dramatically to the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies indicated that propofol can facilitate alfentanil in pain treatment, but the underlying regulatory mechanisms are still unknown. GABA reportedly plays a role in the spinal cord control of nociception .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that propofol can facilitate alfentanil in pain treatment, but the underlying regulatory mechanisms are still unknown. GABA reportedly plays a role in the spinal cord control of nociception .…”
Section: Discussionmentioning
confidence: 99%